Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.3892/ijo_00000170
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling reveals overexpression of TSPAN13 in prostate cancer

Abstract: Abstract. Prostate cancer is one of the most frequent malignancies in the Western world. The identification of additional molecular markers is needed to refine the diagnosis of prostate cancer and to develop more effective therapies. In order to identify molecular abnormalities involved in prostate cancer progression, we performed gene expression analysis of prostate cancer samples compared to matched normal tissue from the same patient using a cancer-related microarray. Amplified RNA was hybridized to a cDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…E2F5 is part of the E2F family that regulates cell cycle interacting with tumor suppressors [42] and has been implicated in malignancy in ovarian cancers [43]. TSPAN13 has been recently found overexpressed in prostate cancers and neoplasia respect to normal [44]. These results support our findings for oncogene-like profiles.…”
Section: Resultssupporting
confidence: 88%
“…E2F5 is part of the E2F family that regulates cell cycle interacting with tumor suppressors [42] and has been implicated in malignancy in ovarian cancers [43]. TSPAN13 has been recently found overexpressed in prostate cancers and neoplasia respect to normal [44]. These results support our findings for oncogene-like profiles.…”
Section: Resultssupporting
confidence: 88%
“…Of these 10 antigens, five corresponded to the IgGs that exhibited the highest-fold increases in level post-treatment (LGALS3, ANPEP, ECE1, FBXO6, and CACNG1); LGALS3 (3638), ANPEP (3941), ECE1 (4245) are known to be expressed at high levels in prostate tumors or to have functional roles in prostate cancer development. We selected the remaining five antigens based on reported functional relevance in cancer and/or increased expression in prostate tumors, viz., KLK2 (4648), E-Ras (49), K-Ras (35), TSPAN13 (50), and LGALS8 (36, 51). Descriptions of the 10 candidate antigens are provided in Supplementary Results.…”
Section: Resultsmentioning
confidence: 99%
“…We found TSPAN13 knockdown repressed the mesenchymal properties in the cell. Cell cycle arrest at G0//G1 phase followed by TSPAN13 depletion in breast cancer was monitored by Zhuchao et al We found that cells were arrested at G0/G1 phase following TSPAN13 knockdown in U2OS cells. To confirm whether arrested dead cell are because of apoptosis or necrosis, BCL‐2, and BAX expression level were observed which confirmed that cells were arrested due to apoptosis.…”
Section: Discussionmentioning
confidence: 93%
“…Tetraspanin‐13 is an uncharacterized member of tetraspanin superfamily and is mainly involve in human tumorigenesis . It is reported that knocking down of TSPAN13 in breast cancer cells enhances the apoptosis of the cells . We have observed that TSPAN13 knockdown in U2OS cells reduces cell viability, clonogenic efficiency and cell migration potential, and enhances the apoptosis of cells.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation